Analisis Biaya Produksi dan Profitabilitas Pada Pabrik Gula Kebon Agung Malang - Anggraeni, Ayu Dewi; jadi, Moel (Jurnal Ilmiah Mahasiswa FEB, 2013)
Sugar  is one of  the strategic commodities  in  Indonesian economy. National sugar production comes mostly  from  sugar  production  in  East  Java.  It  is  based  on  data  from  East  Java  Plantation Office (2007), which states that the rapid growth of the sugar industry in East Java province put Java as the largest contribution to the national sugar production reached 2.31 million tons (over 47 percent) in in 2006. This study aims to determine how the cost of production that occurred as a reference for determining the selling price and to find out how the profitability of the acquired PG Kebun Agung Malang 2010-2012. This  research  is descriptive  research with quantitative approach. Object of  this  study  is PG Kebun Agung Malang.  Sources  of  data  used  in  this  study  is  a  secondary  data  source,  ie  from  production data,  sales  data,  and  the  income  statement.  Data  collection  techniques  used  are  documentation. Analytical  approach  to  the  calculation  of  cost  of  production  using  components  of  the  cost  of materials, direct labor costs, and factory overhead costs. Financial performance analysis in this study using the approach break event analysis (Break Event Point). The results showed that the cost of production that occurred as a reference for determining the selling price in the period 2010-2012 PG Kebon Agung Malang has increased, it indicates that the company can  set  prices  according  to  production  costs  incurred.  The  profitability  derived  from  PG  Kebon Agung Malang in 2010-2012 has decreased, this is due to both fixed costs and operational costs have increased and this will affect the revenue received has decreased. Keyword :Production Cost and Profitability.